Serum Glutaredoxin Activity as a Marker of Oxidative Stress in Chronic Kidney Disease: A Pilot Study - Levin, Anna; Nair, Deepika; Qureshi, Abdul Rashid; Bárány, Peter; Heimburger, Olof; Anderstam, Björn; Stenvinkel, Peter; Bruchfeld, Annette; Ungerstedt, Johanna S (Nephron (2015), 2018)
Inflammation and oxidative stress play important roles in the pathogenesis and progression of chronic kidney disease (CKD) and in its complications, in particular cardiovascular disease, a major cause of death among patients undergoing dialysis treatment. We recently described that Glutaredoxin1 (Grx), an intracellular antioxidant, catalyzes oxidoreductase reactions also extracellularly, and that serum Grx levels correlate to disease severity in type 2 diabetes. In the current study we assess Grx as a potential clinical marker of oxidative stress in CKD. We examined Grx activity in 25 patients with different stages of chronic kidney failure, 19 control subjects, and 36 patients at initiation of dialysis and after 2 years of dialysis. We found that Grx activity was significantly higher in CKD patients compared to control subjects, indicating an oxidized extracellular environment in CKD. Grx levels correlated to interleukin-6 and pentosidine, but not to age or GFR. In dialysis patients with Grx sampling before dialysis start and after 2 years of dialysis, Grx levels increased more in hemodialysis (HD) patients than in peritoneal dialysis patients, indicating an increased oxidative stress imbalance in HD patients. Patients who experienced a stroke or myocardial infarction at any time had a significantly higher increase in Grx during the 2 years of dialysis, compared to patients without stroke or myocardial infarction, indicating a possible association between high Grx levels and a cardiovascular event. Our pilot study indicates that Grx may be a useful marker for assessing the degree of oxidative stress in CKD, however this needs further investigation in a larger prospective patient cohort.